High rate of cardiac thrombus diagnosed by adding cardiac imaging in acute stroke computed tomography protocol. Issue 6 (August 2021) - Bernard, Angélique; Leclercq, Thibault; Comby, Pierre-Olivier; Duloquin, Gauthier; Ricolfi, Frédéric; Béjot, Yannick; Guenancia, Charles
Background: Detection of left atrial appendage thrombus (LAAt) in acute stroke patients can be improved by cardiac computed tomography using prospective electrocardiogram-gated volume acquisition, which was added to the acute stroke computed tomography protocol in our institution in 2018. Aims: To evaluate the factors and clinical management associated with LAAt in patients with acute ischemic stroke. Methods: We retrospectively included 324 consecutive patients with ischemic stroke from November 2018 to October 2019. Clinical data and post-stroke management were compared in LAAt and no-LAAt patients. Results: Thirty-five patients (10.8%; 95%CI 7.4–14.2) had LAAt and 289 had no-LAAt. LAAt patients were significantly older (82 ± 12 vs. 74 ± 14 yo for no-LAAt, p = 0.002), predominantly female (71% vs. 45%, p = 0.004), and were more likely to have previous atrial fibrillation (63% vs. 15%, p < 0.001) and previous stroke (32% vs. 14%, p = 0.005). There was no significant difference between groups in stroke localization or severity scales at admission or at hospital discharge. After multivariable analysis, female sex (odds ratio 2.51; 95%CI 1.09–5.77, p = 0.031), previous atrial fibrillation (odds ratio 4.87; 95%CI 2.11–11.22, p < 0.001), and left atrial volume >86 ml (odds ratio 5.33; 95%CI 1.70–16.69, p = 0.004) were independently associated with LAAt. More than a third of LAAt patients (37%) received acute heparin therapy compared to 13% of no-LAAt patients (p < 0.001). Moreover, despite comparable stroke severity at admission, the mortality rate was markedly higher in the LAAt group than in the no-LAAt group (37% vs. 13%, p < 0.001). Conclusions: Cardiac computed tomography for left atrial appendage thrombus evaluation in routine acute stroke imaging protocol could be beneficial for decision-making with regard to the initiation of early anticoagulation.